Nucleophilic stabilization of water-based reactive ink for titania-based thin film inkjet printing. (February 2017) - Gadea, C.; Marani, D.; Esposito, V.
Abstract: Drop on demand deposition (DoD) of titanium oxide thin films (<500 nm) is performed via a novel titanium-alkoxide-based solution that is tailored as a reactive ink for inkjet printing. The ink is developed as water-based solution by a combined use of titanium isopropoxide and n-methyldiethanolamine (MDEA) used as nucleophilic ligand. The function of the ligand is to control the fast hydrolysis/condensation reactions in water for the metal alkoxide before deposition, leading to formation of the TiO2 only after the jet process. The evolution of the titanium-ligand interactions at increasing amount of MDEA is here elucidated in terms of long term stability. The ink printability parameter (Z) is optimized, resulting in a reactive solution with printability, Z, >1, and chemical stability up to 600 h. Thin titanium oxide films (<500 nm) are proved on different substrates. Pure anatase phase is obtained after annealing at low temperature ( ca . 400 °C). Graphical abstract: Highlights: A new titanium-alkoxide-based solution is tailored as smart ink for inkjet printing. The optimized ink is stable, printable and reactive when deposited on the substrates. Thin films are deposited on various substrates as micron-resolution complex pattern.